Semantic Roles in Joko Widodo Re-Elected as President of BBC Online News - Maria Devi Sidabutar; Zakrimal Zakrimal (Linguistic, English Education and Art (LEEA) Journal, 2020)
This research focused in analyzing the types and the dominant of Semantic Roles that found in Joko Widodo re-elected as President in BBC Online News (2019). The research design of this study is descriptive qualitative. This research used Riemer (2010) theory. The data source of this research was “Joko Widodo re-elected as President” in BBC Online News which was taken from the internet. The method in collecting the data of this research was observation with non-participatory technique by using the transcript. The conclusion was the eight types of semantic roles can be found of Joko Widodo re-elected as President in BBC Online. These data had been collected, the researcher found 10 data that produce 24 results of semantics roles which were involved into eight (8) types, such as; agent (3), patient (2), theme (5), location (2), experiencer (4), instruments (3), goal (2), and source (3) as the results. Also, the dominant types of the semantic roles that frequently appeared was theme and the least was patient, location, and goal. Keywords : Semantic, News, Types of Semantic Roles.